2016
DOI: 10.1177/0886260516651624
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Environmental Predictors of Depression Among Victims of Intimate Partner Violence: Comparison of Immigrant and Israeli-Born Women

Abstract: In the present study, ecological theory was used as a basis for predicting depression among women who survive intimate partner violence (IPV). The predictors examined in the study derived from three ecological systems: the microsystem (background variables and frequency of the violence), the ontogenic system (personal resources), and the mesosystem (support resources). One hundred twenty-five women who immigrated from the Former Soviet Union and 149 Israeli-born Jewish women filled in questionnaires when they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Bronfenbrenner's (1995Bronfenbrenner's ( , 2005 ecological model was used as a framework for synthesizing the various HB risk factors. The choice to use this model stems from the fact that this multilevel socioecological framework of analysis proved fruitful when analyzing a crime's risk factors (Collin-Vézina et al, 2015;Harvey, 2007;Hong et al, 2012;McClaren & Hawe, 2005;Refaeli et al, 2019;Stout, 1992) and its effects on victims (Campbell et al, 2009;Neville et al, 2004). Bronfenbrenner's (1995Bronfenbrenner's ( , 2005 conceptualization identifies four main interrelated social systems that an individual is both influenced by and influences micro, meso-, exo-, and macro-systems.…”
Section: Methodsmentioning
confidence: 99%
“…Bronfenbrenner's (1995Bronfenbrenner's ( , 2005 ecological model was used as a framework for synthesizing the various HB risk factors. The choice to use this model stems from the fact that this multilevel socioecological framework of analysis proved fruitful when analyzing a crime's risk factors (Collin-Vézina et al, 2015;Harvey, 2007;Hong et al, 2012;McClaren & Hawe, 2005;Refaeli et al, 2019;Stout, 1992) and its effects on victims (Campbell et al, 2009;Neville et al, 2004). Bronfenbrenner's (1995Bronfenbrenner's ( , 2005 conceptualization identifies four main interrelated social systems that an individual is both influenced by and influences micro, meso-, exo-, and macro-systems.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that IPV has implications for women’s mental health, and one of the most prevalent mental health variables subject to the influence of IPV is depression (Coker et al, 2002; Kulwicki, Ballout, Kilgore, Hammad, & Dervartanian, 2015; Refaeli, Levy, Ben-Porat, Dekel, & Itzhaky, 2016; Rodriguez et al, 2008; Wong, Tiwari, Fong, & Bullock, 2016). Specifically, exposure to IPV has been found to increase its risk (Bean & Moller, 2002; Cascardi, O’Leary, & Schlee, 1999; Kessler, Molnar, Feurer, & Appelbaum, 2001).…”
Section: Depression Among Women Who Are Victims Of Violencementioning
confidence: 99%
“…IPV is a recurrent scenario in which women feel that they lack control over their situations and in which they often have difficulty predicting what will trigger the next episode of violence (Walker, 2009). Studies conducted among women who have experienced IPV have revealed that there is a relationship between the women’s sense of mastery and their symptoms of depression (Bargai et al, 2007; Refaeli et al, 2016; Rodriguez et al, 2008). The findings of these studies further indicate that a high sense of mastery is associated with lower levels of depression and hopelessness (Clements, Sabourian, & Spiby, 2004; Clements & Sawhney, 2000; Kim & Gray, 2008; Meadows, Kaslow, Thompson, & Jurkovic, 2005).…”
Section: Personal Resources: Sense Of Mastery and Depressionmentioning
confidence: 99%
“…Previous studies have shown that post-disaster stress increases the prevalence of violence against women ( Anastario et al, 2009 ; Yoshihama et al, 2013 ). Studies have found that intimate partner violence (IPV)is a significant factor associated with depression ( Chandan et al, 2020 ; Refaeli et al., 2019 ). IPV is a serious and preventable public health problem that affects millions.…”
Section: Introductionmentioning
confidence: 99%